Contemporary trends in the management of aortic stenosis in the USA. (13th August 2019) - Alkhouli, Mohamad; Alqahtani, Fahad; Ziada, Khaled M; Aljohani, Sami; Holmes, David R; Mathew, Verghese
Abstract: Aims: To assess the contemporary trends in aortic stenosis (AS) interventions in the USA before and after the introduction of transcatheter aortic valve implantation (TAVI). Methods and results: We utilized the National-Inpatient-Sample to assess temporal trends in the incidence, cost, and outcomes of AS interventions between 1 January 2003 and 31 December 2016. During the study's period, AS interventions increased from 96 to 137 per 100 000 individuals > 60 years old, P < 0.001. In-hospital expenditure on AS interventions increased from 2.28 billion in 2003 to 4.33 in 2016 P < 0.001. Among patients who underwent aortic valve replacement, the proportion of TAVI increased from 11.9% in 2012 to 43.2% in 2016 ( P < 0.001). Males and Hispanics had lower proportions of TAVI compared with females and White patients. Adjusted in-hospital mortality of isolated SAVR decreased from 5.4% in 2003 to 3.3% in 2016 ( P < 0.001), whereas adjusted in-hospital mortality of TAVI decreased from 4.7% in 2012 to 2.2% in 2016, P < 0.001. The incidence of new dialysis, permanent pacemaker implantation, and blood transfusion decreased after both TAVI and SAVR between 2012 and 2016. However, the rate of post-operative stroke did not significantly decrease. Length of stay and cost of hospitalization decreased after both SAVR and TAVI, although the later remained higher with TAVI. Rates of non-home discharge decreased over time after TAVI but remained stable after isolated SAVR. Conclusion: This nationwide survey documents the increasing incidence of AS interventions, the rising cost of modern AS care, and the paradigm shift in aortic valve replacement practice in the USA.